Respuesta :
x(x + 1) = 72
Expanding the brackets, we get:
[tex]x^{2}+x=72[/tex]
Subtracting 72 from both sides, gives:
[tex]x^{2}+x-72=0[/tex]
This is the required equation to be factored and solved .
Expanding the brackets, we get:
[tex]x^{2}+x=72[/tex]
Subtracting 72 from both sides, gives:
[tex]x^{2}+x-72=0[/tex]
This is the required equation to be factored and solved .
x(x + 1) = 72
x² + x = 72
x² + x - 72 = 0
The first option from the top.
x² + x = 72
x² + x - 72 = 0
The first option from the top.